Analgesic, anti-inflammatory and antipyretic properties of Acacia suma stem bark - Sumanta Mondal,; S. Raja,; P Suresh,; G S Kumar, (International Journal of Phytomedicine, 2013)
Acacia suma (Fabaceae) is a medium sized erect tree found in the greater part of India. Present study was carried out for evaluation of ethanolic extract of stem bark of Acacia suma (EEAS) at 200 and 400 mg/kg, p.o. for analgesic, anti-inflammatory and antipyretic activity. EEAS was screened for analgesic activity by writhing, tail flick, tail immersion and hot plate method in mice. The anti-inflammatory activity by acute carrageenan induced paw oedema and chronic Freund’s adjuvant arthritis models in rats. The antipyretic activity was evaluated using Brewer’s yeast induced pyrexia in rabbits. Acute toxicity in mice was found to be higher than 2000 mg/kg., p.o. Analgesic activity revealed that test dose of 400 mg/kg, p.o., had significant activity in various tested models. Anti-inflammatory studies at 200 and 400 mg/kg., p.o., of extract showed significant activity (P<0.01). The extract showed significant (P<0.01) effect on yeast-induced fever in rabbits in dose dependant manner. Preliminary phytochemical tests revealed presence of carbohydrates, tannins, alkaloids, saponins and phenolic compounds in the ethanol extract of A. suma bark. The present study therefore provides scientific base for its use in the folklore remedies as an analgesic, anti-inflammatory and antipyretic properties of natural origin.